The effect of accounting conservatism on the cost of equity with information asymmetry as an intervening variable and corporate governance as a moderator - Ade Hanifah Sari; Anies Lastiati (LPMP Imperium, 2025)
This study aims to examine the relationship between accounting conservatism and the cost of equity, both directly and indirectly, and to test the role of information asymmetry as an intervening variable with corporate governance as a moderating variable. The research employs a quantitative method. The sampling technique was determined using purposive sampling. The data type used is secondary data obtained from companies in the Property, Real Estate, and Building Construction sectors listed on the Indonesia Stock Exchange during the 2016-2017 period. The total sample consists of 72 companies. The difference between this study and previous ones lies in analyzing whether the direct or indirect relationship between accounting conservatism and the cost of equity has a more significant effect. Additionally, this study incorporates corporate governance as a moderating variable. The results indicate that accounting conservatism's direct influence on the cost of equity is greater than the indirect effect mediated by information asymmetry. Thus, accounting conservatism has a more significant direct impact on the equity price. Meanwhile, corporate governance is proven to moderate the relationship between accounting conservatism and information asymmetry, and the relationship is significantly positive. Public interest statementsThis research benefits the general public by providing practical insights on how accounting conservatism and good corporate governance can improve the transparency of financial information. It helps stakeholders, especially investors, make smarter investment decisions by minimizing the risk of asymmetric information.